The Influence of Eco-Efficiency, Green Accounting, and Corporate Social Responsibility (CSR) on The Financial Performance of Manufacturing Companies Listed on Indonesia Stock Exchange - Tiyas, Diska Cahyaning; Imronudin, I (Universitas Muhammadiyah Surakarta, 2024)
Purpose: The purpose of this research is to evaluate how eco-efficiency, green accounting practices, and corporate social responsibility (CSR) influence the financial performance of manufacturing firms listed on the Indonesian Stock Exchange. Manufacturing companies have a direct connection to the social problems associated with the company's operations. Public awareness of sustainability plays a crucial role in driving companies to focus on their environmental responsibilities, as reflected in their annual sustainability reports. Companies that implement environmental accountability receive positive feedback from the public so that they can improve their operational and financial performance. Financial performance becomes an important measure that investors use to insert their modalities into manufacturing companies. Methodology: This study uses multiple linear regression analysis as the analytical method. Eco-efficiency is measured on the basis of implementation of eco-efficiency of the amount of production with the use of electricity. Green accounting measures participation in the PROPER Programme, corporate social responsibility (CSR) measures the environmental cost, while financial performance measures return on asset (ROA). Results: The findings of this study indicate that eco-efficiency, green accounting, and corporate social responsibility do not individually affect financial performance. However, when considered together, these factors have a significant simultaneous impact on financial performance. Applications/Originality/Value: The researchers hope this research can help investors identify companies that have better financial performance through sustainable practices, as well as help manufacturing companies in designing policies that support sustainable development in the manufacturing sector.